RISE AND FALL OF MAMLUK SULTANATE: The Struggle Against Mongols and Crusaders in Holy War - Firdaus, Yelmi Eri; Elfia, Elfia; Meirison, Meirison (Universitas Islam Negeri Imam Bonjol Padang, 2020)
For 300 years, precisely from 1250 to 1517, the Mamluk Dynasty ruled in Egypt and Syria. Their power ended after the conquest of the Ottoman Turks, who later built a new empire. The writer wants to describe how the slave nation could become a ruler who gained legitimacy from Muslims. Mamluk is a soldier who comes from slaves who have converted to Islam.